The Influence of Leadership Behavior and Work Motivation on Service Quality at the Population and Civil Registration Office of Boalemo Regency - Adnan Marzuk; Arifin Tahir; William I. S. Mooduto (LP2M Universitas Bina Mandiri Gorontalo, 2020)
The purpose of this research is: 1) to find out and explain partially the influence of leadership behavior on the quality of population administration services at the Population and Civil Registration Office of Boalemo Regency; 2) to find out and explain there is a partial influence of employee work motivation on the quality of population administration services at the Population and Civil Registration Office of Boalemo Regency; 3) to find out and explain there is a simultaneous influence between leadership behavior and employee work motivation on the quality of population administration services at the Population and Civil Registration Office of Boalemo Regency. Quantitative descriptive research method approach with survey research type that explains the caesal relationship and conduct hypothesis testing with multiple regression analysis approach. The results showed that:1) There is a positive and significant influence between leadership behavior on service quality at the Population and Civil Registration Office of Boalemo Regency, which means that the better the behavior of a leader, the better the quality of service; 2) There is a positive and significant influence between work motivation on service quality at the Population and Civil Registration Office of Boalemo Regency, which means that the increase in employee motivation, the better the service provided; 3) There is a positive and significant influence between leadership behavior and work motivation on the quality of service at the Population and Civil Registration Office of Boalemo Regency, which means that the increase in employee work motivation, the better the service provided.